2016
DOI: 10.6066/jtip.2016.27.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Stabilitas Fotooksidasi Minyak Goreng Sawit Yang Difortifikasi Dengan Minyak Sawit Merah

Abstract: Deterioriation of palm oil fortified with vitamin A and provitamin A could b e caused b y the presence of oxygen and light exposure. The purpose of this study was to determine the effect of the initial peroxide value (PV) in palm oil (1.99, 3.98, and 9.95 meq O2/kg oil) and light intensity (15000, 10000, and 5000 lux) on the rate of oxidation and the shelf life of palm oil fortified with Red Palm Oil (RPO) equal to 45 IU vitamin A. The RPO contained β-carotene as provitamin A in the amount of 504.67 ppm. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
0
0
3
Order By: Relevance
“…Therefore, in the purification process, both degumming and neutralization could trigger a hydrolysis reaction especially due to washing steps [7]. Meanwhile, Andarwulan et al [34] reported that during storage of palm cooking oil which passed through the refining process, i.e, degumming, neutralization, bleaching and deodorization with a very low water content, the formation rate of peroxide is higher than that of FFAs [34]. The presence of minute water in the final refined oil is a critical point in quality assurance of oil.…”
Section: Kinetics Of Deterioration Of the Nrfo During Storagementioning
confidence: 99%
“…Therefore, in the purification process, both degumming and neutralization could trigger a hydrolysis reaction especially due to washing steps [7]. Meanwhile, Andarwulan et al [34] reported that during storage of palm cooking oil which passed through the refining process, i.e, degumming, neutralization, bleaching and deodorization with a very low water content, the formation rate of peroxide is higher than that of FFAs [34]. The presence of minute water in the final refined oil is a critical point in quality assurance of oil.…”
Section: Kinetics Of Deterioration Of the Nrfo During Storagementioning
confidence: 99%
“…Rendemen produk CPO ternetralisasi pada suhu 50-90°C yang diperoleh sebesar 73,8-77,1%. Rendemen sangat dipengaruhi oleh proses yang dihasilkan penelitian ini lebih rendah dibandingkan dengan yang dilaporkan oleh Widarta et al, (2012) yaitu 90,16%. Hal ini dikarenakan Widarta et al, (2012) melakukan sentrifugasi terlebih dahulu untuk memisahkan sabun kemudian dicuci dengan air panas, sedangkan pada penelitian ini dilakukan pencucian langsung, sehingga diduga minyak terjerap dan tercuci pada air cucian sabun.…”
Section: Hasil Dan Pembahasan Pembuatan Minyak Sawit Merah (Msm) Skal...unclassified
“…Rendemen sangat dipengaruhi oleh proses yang dihasilkan penelitian ini lebih rendah dibandingkan dengan yang dilaporkan oleh Widarta et al, (2012) yaitu 90,16%. Hal ini dikarenakan Widarta et al, (2012) melakukan sentrifugasi terlebih dahulu untuk memisahkan sabun kemudian dicuci dengan air panas, sedangkan pada penelitian ini dilakukan pencucian langsung, sehingga diduga minyak terjerap dan tercuci pada air cucian sabun. pencucian, dimana pada suhu tinggi relatif mudah dilakukan karena pemisahaan antara minyak dan air cukup jelas sehingga tidak banyak minyak yang terbuang atau tercuci.…”
Section: Hasil Dan Pembahasan Pembuatan Minyak Sawit Merah (Msm) Skal...unclassified
See 1 more Smart Citation